Pelatihan Penyusunan Laporan Keuangan untuk Menciptakan Akuntabilitas Badan Usaha Milik Desa (BUMDes) - Mohammad Herli; Edy Purwanto; Hafidhah Hafidhah; Suryani Dwi Kuswardhini; Rizal Dani Sya’bana (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
BUMDes is a pillar of village development that aims to equalize the economy in rural areas. The development of BUMDes can support strengthening village income to be more independent. BUMDes has a very important role as a collective economic institution that aims to optimize the welfare of rural communities. The basic problem of rural development is the limited authority. Most rural development methods place villagers only as objects of development dan not as subjects who have the strategic dan decisive authority to manage village assets. In addition, BUMDes still experience various obstacles, including lack of capital, limited human resource capacity in managing BUMDes dan lack of BUMDes socialization activities. This PKM activity aims to strengthen the management of BUMDes, especially in financial governance. This stage is very important so that the financial governance of BUMDes is more structured dan in accordance with the strategy dan direction of the accountability policy. The implementation method includes training dan assistance in preparing BUMDes financial reports which include planning dan preparing periodic audit financial report documents. Thus, it is hoped that BUMDes managers can carry out good financial governance dan accountability in BUMDes financial reporting is realized. The implementation of this PKM activity was carried out in Lembung Timur Village, Lenteng District, Sumenep Regency. The results of the activity showed that there was an increase in knowledge dan understdaning of BUMDes management in Lembung Timur Village about the importance of financial management. BUMDes management understdans financial management procedures in terms of planning dan preparing financial report documents. It is hoped that after this activity, BUMDes in the village will be able to prepare financial reports to support the sustainability of their business.